Presence of Left Atrial Fibrosis May Contribute to Aberrant Hemodynamics and Increased Risk of Stroke in Atrial Fibrillation Patients - Paliwal, Nikhil; Ali, Rheeda L.; Salvador, Matteo; O’Hara, Ryan; Yu, Rebecca; Daimee, Usama A.; Akhtar, Tauseef; Pandey, Pallavi; Spragg, David D.; Calkins, Hugh; Trayanova, Natalia A. (Frontiers in Physiology, 2021)
Atrial fibrillation (AF) patients are at high risk of stroke, with the left atrial appendage (LAA) found to be the most common site of clot formation. Presence of left atrial (LA) fibrosis has also been associated with higher stroke risk. However, the mechanisms for increased stroke risk in patients with atrial fibrotic remodeling are poorly understood. We sought to explore these mechanisms using fluid dynamic analysis and to test the hypothesis that presence of LA fibrosis leads to aberrant hemodynamics in the LA, contributing to increased stroke risk in AF patients. We retrospectively collected LGE-MRI images of 8 AF patients (4 persistent and 4 paroxysmal) and reconstructed their 3D LA surfaces. Personalized computational fluid dynamic simulations were performed, and hemodynamics at the LA wall were quantified by wall shear stress (WSS, friction of blood), oscillatory shear index (OSI, temporal directional change of WSS), endothelial cell activation potential (ECAP, ratio of OSI and WSS) and relative residence time (RRT, residence time of blood near the LA wall). For each case, these hemodynamic metrics were compared between fibrotic and non-fibrotic portions of the wall. Our results showed that WSS was lower and OSI, ECAP and RRT was higher in the fibrotic region as compared to the non-fibrotic region, with ECAP (p=0.001) and RRT (p=0.002) having significant differences. Case-wise analysis showed that these differences in hemodynamics were statistically significant for 7 cases. Furthermore, patients with higher fibrotic burden were exposed to larger regions of high ECAP, which represents regions of low WSS and high OSI. Consistently high ECAP in the vicinity of the fibrotic wall suggest that local blood-flow was slow and oscillating that represents aberrant hemodynamic conditions, thus enabling pro-thrombotic conditions for circulating blood. AF patients with high LA fibrotic burden had more pro-thrombotic regions, providing more sites for potential clot formation, thus increasing their risk of stroke.